Wittgenstein on Elucidations. Introduction to "Tractatus logico-philosophicus" - Bogucki, Krystian (Hybris, 2018)
In this article I examine some remarks from Wittgenstein‘s Tractatus logico-philosophicus about the point and the method of his work. First part of the article concerns relationships between Frege‘s conception of elucidation and Wittgenstein‘s conception of philosophy. Second part of the article is about Wittgenstein‘s attitude to science and the role of science in philosophy. Third part of my article concerns the ethical purpose of Wittgenstein‘s Tractatus logico-philosophicus.